Fundamentals of Insight Meditation - Vangkonevilay, Nilandon (BUDDHO, 2023)
This study examines the contemporary interpretation and application of Buddhist epistemology in relation to mindfulness and cognitive processes in modern society. The primary objectives of the research are: (1) to analyze key epistemological concepts in early Buddhist texts, particularly perception and cognition; (2) to explore their reinterpretation in modern psychological discourse; and (3) to evaluate their practical relevance in contemporary mental health contexts. The study employs a qualitative research methodology, utilizing documentary analysis of primary sources from the Pāli Canon and selected Mahāyāna texts, alongside scholarly works in Buddhist studies and cognitive science. The study population consists of canonical scriptures, academic publications, and contemporary research articles relevant to Buddhist epistemology and mindfulness theory. Research tools include textual analysis, comparative analysis, and thematic synthesis. Data were analyzed through interpretative and critical methods to identify conceptual parallels and divergences between traditional Buddhist thought and modern cognitive frameworks. The findings reveal that Buddhist theories of perception emphasize conditioned cognition, non-self (anattā), and dependent origination as foundational to understanding mental processes. These principles demonstrate significant conceptual resonance with contemporary psychological models of cognition and mindfulness-based therapeutic approaches. The study contributes to the body of knowledge by clarifying the philosophical foundations of mindfulness practices and highlighting the interdisciplinary relevance of Buddhist epistemology in modern scientific discourse. It further suggests that integrating classical Buddhist insights with empirical research may enrich both philosophical inquiry and applied psychological practice.